CHARM QUARK PRODUCTION AND FRAGMENTATION IN E+E- ANNIHILATION AT 29 GEV - Derrick, M; Fernandez, E; Fries, R; Hyman, L; Kooijman, P; Loos, J; Musgrave, B; Price, L; Schlereth, J; Sugano, K; Weiss, J; Wood, D; et al. (1984)
The electroweak production asymmetry and the decay fragmentation function for e+e- → cc have been measured at s = 29 GeV using charged D* production over the full kinematic range. The data were taken at PEP using the High Resolution Spectrometer. The measured asymmetry is -0.12 ± 0.08. The total production cross section in units of the point cross section corrected for initial state radiation is RD* = 2.7 ± 0.9. © 1984.